Meridional Ocean Carbon Transport. Issue 9 (2nd September 2020) - Aldama‐Campino, Aitor; Fransner, Filippa; Ödalen, Malin; Groeskamp, Sjoerd; Yool, Andrew; Döös, Kristofer; Nycander, Jonas
Abstract : The ocean's ability to take up and store CO2 is a key factor for understanding past and future climate variability. However, qualitative and quantitative understanding of surface‐to‐interior pathways, and how the ocean circulation affects the CO2 uptake, is limited. Consequently, how changes in ocean circulation may influence carbon uptake and storage and therefore the future climate remains ambiguous. Here we quantify the roles played by ocean circulation and various water masses in the meridional redistribution of carbon. We do so by calculating streamfunctions defined in dissolved inorganic carbon (DIC) and latitude coordinates, using output from a coupled biogeochemical‐physical model. By further separating DIC into components originating from the solubility pump and a residual including the biological pump, air‐sea disequilibrium, and anthropogenic CO2, we are able to distinguish the dominant pathways of how carbon enters particular water masses. With this new tool, we show that the largest meridional carbon transport occurs in a pole‐to‐equator transport in the subtropical gyres in the upper ocean. We are able to show that this pole‐to‐equator DIC transport and the Atlantic meridional overturning circulation (AMOC)‐related DIC transport are mainly driven by the solubility pump. By contrast, the DIC transport associated with deep circulation, including that in Antarctic bottom water and Pacific deep water, is mostly driven by the biological pump. As these two pumps, as well as ocean circulation, are widely expected to be impacted by anthropogenic changes, these findings have implications for the future role of the ocean as a climate‐buffering carbon reservoir. Key Points: Quantification of redistribution of DIC by ocean meridional circulation is related to physical and biological processes Transports of solubility carbon dominates the upper ocean and the NADW, biogenic carbon the deep ocean Pacific biological pump is the most important process retaining carbon on longer time scales